Eco-Friendly Iron-Humic Nanofertilizers Synthesis for the Prevention of Iron Chlorosis in Soybean (Glycine max) Grown in Calcareous Soil - Cieschi, María T.; Polyakov, Alexander Yu; Lebedev, Vasily A.; Volkov, Dmitry S.; Pankratov, Denis A.; Veligzhanin, Alexey A.; Perminova, Irina V.; Lucena, Juan J. (Frontiers in Plant Science, 2019)
Iron deficiency is a frequent problem for many crops, particularly in calcareous soils and iron humates are commonly applied in the Mediterranean basin in spite of their lesser efficiency than iron synthetic chelates. Development and application of new fertilizers using nanotechnology are one of the potentially effective options of enhancing the iron humates, according to the sustainable agriculture. Particle size, pH and kinetics constrain the iron humate efficiency. Thus, it is relevant to understand the iron humate mechanism in the plant-soil system linking their particle size, characterization and iron distribution in plant and soil using 57Fe as a tracer tool. Three hybrid nanomaterials (F, S and M) were synthesized as iron humic nanofertilizers (57Fe-NFs) from leonardite potassium humate and 57Fe used in the form of 57Fe(NO3)3 or 57Fe2(SO4)3. They were characterized using Mössbauer spectroscopy, X-Ray Diffraction (XRD), Extended X-Ray Absorption Fine Structure spectroscopy (EXAFS), Transmission Electron Microscopy (TEM) and tested for iron availability in a calcareous soil pot experiment carried out under growth chamber conditions. Three doses (35, 75 and 150 µmol pot-1) of each iron-humic material were applied to soybean iron deficient plants and their iron nutrition contributions were compared to 57FeEDDHA and leonardite potassium humate as control treatments. Ferrihydrite was detected as the main structure of all three 57Fe-NFs and the plants tested with iron-humic compounds exhibited continuous long term statistically reproducible iron uptake and showed high shoot fresh weight. Moreover, the 57Fe from the humic nanofertilizers remained available in soil and was detected in soybean pods. The Fe-NFs offers a natural, low cost and environmental option to the traditional iron fertilization in calcareous soils.